1993
DOI: 10.1128/iai.61.6.2558-2562.1993
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibody to Haemophilus somnus in the bovine uterus following intramuscular immunization

Abstract: Sources of anti-Haemophilus somnus antibody in bovine uterine secretions following intramuscular immunization and subsequent intrauterine inoculation of killed H. somnus were investigated. Holstein cattle (n = 21) were immunized with a 270-kDa outer membrane protein from H. somnus (omp-270) by intramuscular injection. At estrus, the cattle were given an intrauterine inoculum of a heat-killed suspension of a homologous strain of H. somnus containing omp-270 (n = 7), a heterologous strain of H. somnus lacking om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…IgA is made at the mucosal surface of the bovine uterus. The endometrium produces half of the IgG1 fraction, while the balance of the IgG1 and all of the IgG2 come from the peripheral circulation ( 63 ) ( Figure 3 ).…”
Section: Economic Consequences Of Immunoinfertilitymentioning
confidence: 99%
“…IgA is made at the mucosal surface of the bovine uterus. The endometrium produces half of the IgG1 fraction, while the balance of the IgG1 and all of the IgG2 come from the peripheral circulation ( 63 ) ( Figure 3 ).…”
Section: Economic Consequences Of Immunoinfertilitymentioning
confidence: 99%
“…Admittedly, the correlation between circulating and intrauterine NAb levels is not known; however, previous studies have suggested that most of the immunoglobulins found in the uterine secretion of cattle are serum derived (Corbeil et al, 1974;Butt et al, 1993). The idea that antibodies may play an important role in uterine disease resistance is partly supported by a previous study, in which it was reported that systemic immunization against important intrauterine pathogens increased blood levels of specific antibodies and decreased the incidence of puerperal metritis (Machado et al, 2014).…”
Section: Short Communicationmentioning
confidence: 99%
“…Data showing the ability of vaccination to protect against abortion is lacking,56 although the development of a systemic IgG 2 antibody response may provide local immunological protection in the uterus. 13 Like all bacterins, protection from clinical disease is short-lived at best; therefore, a minimum of two primary vaccinations given at month intervals and at least annual boosters would be needed to provide even theoretical protection in those herds where the disease has been demonstrated.…”
Section: Vaccination Protocolmentioning
confidence: 99%